Elevated L1CAM expression in precursor lesions and primary and metastastic tissues of pancreatic ductal adenocarcinoma - Bergmann, Frank; Wandschneider, Frauke; Sipos, Bence; Moldenhauer, Gerhard; Schniewind, Bodo; Welsch, Thilo; Schirmacher, Peter; Klöppel, Günter; Altevogt, Peter; Schäfer, Heiner; Sebens, Susanne (Oncology reports, 2010)
The promigratory molecule L1CAM is overexpressed in various tumors, often representing an unfavorable prognostic marker. Recently, we identified L1CAM expression in pancreatic ductal adenocarcinoma (PDAC) cells accounting for chemoresistance and increased cell migration. Thus, the present study aims at further elucidating the role of L1CAM in a larger cohort of PDAC specimens including precursor lesions and metastasis. L1CAM expression was determined by immunohistochemistry in tissues of 123 patients including tissues of 110 primary PDACs, 15 lymph node metastases and 14 liver metastases. The immunohistochemical analyses revealed L1CAM expression in 92.7% of primary PDACs, 80% of lymph node metastases and 100% of liver metastases. Furthermore, we have investigated PDAC precursors, pancreatic intraepithelial neoplasia (PanIN) lesions, revealing a significant increase of L1CAM expression with the PanIN grade (6.4 and 6.8% in PanIN 1A and B, 35% in PanIN 2 and 20% in PanIN 3). The elevated expression of L1CAM already found in PanINs points to a role of L1CAM quite early in tumorigenesis of PDAC. Furthermore, its broad expression in primary tumors as well as in metastases of PDAC patients provide a rationale to further explore the value of L1CAM as a therapeutic target in the treatment of this highly malignant tumor.
Der Autor "Schirmacher, Peter" schreibt sich mit einem "r" und nicht mit 2 "r" wie im Artikel
Gesehen am 19.01.2023